Crystallization and preliminary X-ray crystallographic analysis of recombinant β-mannosidase from Aspergillus niger - Demo, Gabriel; Fliedrová, Barbora; Weignerová, Lenka; Wimmerová, Michaela (Acta crystallographica. Section F, Structural biology and crystallization communications, 2013)
β-Mannosidase (EC 3.2.1.25) is an important exoglycosidase specific for the hydrolysis of terminal β-linked mannoside in various oligomeric saccharide structures. β-Mannosidase from Aspergillus niger was expressed in Pichia pastoris and purified to clear homogeneity. β-Mannosidase was crystallized in the presence of D-mannose and the crystal diffracted to 2.41 Å resolution. The crystal belonged to space group P1, with unit-cell parameters a=62.37, b=69.73, c=69.90 Å, α=108.20, β=101.51, γ=103.20°. The parameters derived from the data collection indicate the presence of one molecule in the asymmetric unit.
Keywords: Recombinant Proteins; krystalografie rentgenová; mannosa; beta-mannosidasa; Aspergillus niger; Mannose; β-mannosidase; Crystallography, X-Ray; fungální proteiny; Fungal Proteins; krystalizace; rekombinantní proteiny; Pichia; beta-Mannosidase; Crystallization